Tracking Down the Sources of James Stuart's Readers - Wright, John (The Journal of Natal and Zulu history, 2021)
In the period from 1923 to 1926, James Stuart, a former Natal colonial official, produced five readers written in isiZulu for use in Natal's isiZulu-speaking schools. They were uTulasizwe (1923), uHlangakula (1924), uBaxoxele (1924), uKulumetule (1925) and uVusezakiti (1926). Each consisted of a number of izifundo, or 'lessons', on what Stuart would have called Zulu 'history and custom'. They have generally been seen as Stuart's own writings, but research into the six published volumes of the James Stuart Archive has led to the development of a quite different picture. It is now clear that many of the izifundo were drawn, often verbatim, from Stuart's notes on his conversations about the past with specific African interlocutors, who can be named and whose lives, to varying degrees, can be researched. This finding transforms our understanding of the place occupied by Stuart's readers in the historical literature written in isiZulu. As an aid to further research in this field, this article lists the individual interlocutors whom the author has so far been able to identify.